Fuzzy Subtractive Clustering Technique applied to Demand Response in a Smart Grid Scope - Pereira, Rita (2014)
This paper focuses on demand response in a smart grid scope using a fuzzy subtractive clustering technique for modeling demand response. Domestic consumption is classified into profiles in order to favorable cover the adequate modeling. The fuzzy subtractive clustering technique is applied to a case study of domestic consumption demand response with three scenarios and a comparison of the results is presented. The demand response developed model intends to support consumer's decisions given a compromise between the consumption imperative needs and possible economical benefits due to reshape and reschedule.